A cholesterol-lowering VLP vaccine that targets PCSK9. Issue 43 (26th October 2015) - Crossey, Erin; Amar, Marcelo J.A.; Sampson, Maureen; Peabody, Julianne; Schiller, John T.; Chackerian, Bryce; Remaley, Alan T.
Highlights: PCSK9 is a molecule that controls the metabolism of low-density lipoprotein cholesterol (LDL-C). We have generated virus-like particles based vaccines that induce high-titer antibodies against PCSK9. Vaccination of mice with PCSK9-VLPs resulted in reduced lipid levels. Macaques vaccinated with PCSK9-VLPs and coadministered statins had significant reduction in LDL-C levels. Vaccination against PCSK9 may be an alternative to monoclonal antibody-based therapies. Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secretory protein that controls cholesterol homeostasis by enhancing endosomal and lysosomal degradation of the low-density lipoprotein receptor (LDL-R). Mutations that cause increased activity of PCSK9 are associated with hypercholesterolemia, atherosclerosis and early cardiovascular disease (CVD), whereas individuals with loss-of-function mutations in PCSK9 are apparently healthy but are hypocholesterolemic and have a dramatically decreased risk of CVD. In this study, we generated virus-like particle (VLP)-based vaccines targeting PCSK9. Mice and macaques vaccinated with bacteriophage VLPs displaying PCSK9-derived peptides developed high titer IgG antibodies that bound to circulating PCSK9. Vaccination was associated with significant reductions in total cholesterol, free cholesterol, phospholipids, and triglycerides. A vaccine targeting PCSK9 may, therefore, be an attractive alternative to monoclonal antibody-based therapies.